2021
DOI: 10.1038/s42003-021-02327-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiomic analysis of the Arabian camel (Camelus dromedarius) kidney reveals a role for cholesterol in water conservation

Abstract: The Arabian camel (Camelus dromedarius) is the most important livestock animal in arid and semi-arid regions and provides basic necessities to millions of people. In the current context of climate change, there is renewed interest in the mechanisms that enable camelids to survive in arid conditions. Recent investigations described genomic signatures revealing evolutionary adaptations to desert environments. We now present a comprehensive catalogue of the transcriptomes and proteomes of the dromedary kidney and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 128 publications
(179 reference statements)
0
9
0
Order By: Relevance
“…The immune expression in the case of dromedaries showed strong expression of the lining epithelium of collecting tubules and the moderate reaction of the loop of Henle (Khafaga et al, 2021). Altogether, these data strongly suggest that dromedaries can produce highly concentrated urine, which was ensured by Alvira-Iraizoz et al (2021) who revealed that water retention in the kidney indirectly facilitated by the AQP2-mediated water reabsorption. However, the specific function and underlying mechanisms of this observation are not clear and should further be investigated.…”
Section: Discussionmentioning
confidence: 69%
“…The immune expression in the case of dromedaries showed strong expression of the lining epithelium of collecting tubules and the moderate reaction of the loop of Henle (Khafaga et al, 2021). Altogether, these data strongly suggest that dromedaries can produce highly concentrated urine, which was ensured by Alvira-Iraizoz et al (2021) who revealed that water retention in the kidney indirectly facilitated by the AQP2-mediated water reabsorption. However, the specific function and underlying mechanisms of this observation are not clear and should further be investigated.…”
Section: Discussionmentioning
confidence: 69%
“…We looked to one of nature’s water conserving wonders, the camel, to provide answers and molecular insights into the specialisations that ensure survival in these environments. Having recently reported transcriptomic and proteomic adaptations to WD in the camel kidney 40 , we turned our attention to the hypothalamic neuroendocrine mechanisms responsible for orchestrating the response to WD. This is the first time that the camel brain has been so extensively studied in terms of its adaptations to the desert environment.…”
Section: Discussionmentioning
confidence: 99%
“…In Old World camels, de novo whole-genome sequencing including shot-gun, long reads, and structural Hi-C mapping was used to build high-quality reference genomes on chromosome levels ( Elbers et al , 2019 ; Ming et al , 2020 and references therein). Multiomic, i.e., transcriptomic and proteomic analyses of dromedary ( Alvira-Iraizoz et al , 2021 ) and Bactrian camel ( Wu et al , 2014 ) kidney tissues complemented and advanced these important first steps towards understanding the structure and function of camelid genomes. Building on these newly available high-quality reference genomes, polymorphism and structural and functional analyses of targeted regions were performed, and initial genome-wide association studies were launched.…”
Section: Where Do We Stand In Structural and Functional Genomics In C...mentioning
confidence: 99%